Challenges in Supporting Survivors of Child Sexual Abuse in Kenya: A Qualitative Study of Government and Non-governmental Organizations - Wangamati, Cynthia Khamala (Journal of interpersonal violence, 2021)
Child sexual abuse (CSA) is a global, social, and health challenge. Existing literature on post-sexual assault care has focused largely on health providers’ skills and capacity to offer quality clinical, medicolegal, and psychosocial care. Services other than medical and psychosocial care provided to survivors of CSA remain poorly studied, particularly in the global south. The study aimed to explore challenges facing service providers supporting children who have experienced sexual abuse and make suitable recommendations. We triangulated different qualitative methods: in-depth interviews with 61 key informants, three focus group discussions with community leaders, and unstructured observations for data collection. Findings indicate that service providers supporting children who had experienced sexual abuse play a vital role in ensuring that survivors receive clinical and medicolegal care, psychosocial support, have access to justice, and are protected from further victimization. However, these service providers face several challenges, including poor infrastructure, the lack of effective coordination and linkage among the service providers in the continuum of care, corruption among officials, and harmful patriarchal norms that hinder reporting of abuse. To effectively support and care for survivors, we recommend government commitment to, and investments in, safe spaces, supervision, and professional development of providers. Working with community leaders and gatekeepers of all genders is critical to address harmful practices that perpetuate CSA and make it difficult to care for and obtain justice for CSA survivors.